Hexafluorophosphate anion intercalation into graphite electrode from sulfolane/ethylmethyl carbonate solutions. (20th January 2016) - Fan, Hui; Gao, Jichao; Qi, Li; Wang, Hongyu
Abstract: The electrochemical behaviour of graphite positive electrode has been tested in the electrolyte solutions of 1 mol dm −3 LiPF6 dissolved in mixed solvents of sulfolane (SL) and ethylmethyl carbonate (EMC). The suppression of PF6 − anion intercalation into graphite by SL has been demonstrated. Moreover, the favourable effect of EMC on PF6 − insertion into graphite in SL-based solutions has been verified by ex situ XRD, ex situ Raman, and electrochemical tests. Furthermore, improved long-term cycling performance of graphite positive electrode has been obtained in solutions with suitable ratios of SL and EMC.